Identifying if patient's living with heart failure retain knowledge better by gaining it through lived experience rather than through education. (2nd July 2022) - Caples, N; Regan, A; Vijayamma Sadanandan, D; Huish, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Self-care is when a patient possesses a set of knowledge and skills that are used to process information to make correct health decisions. Self-care in heart failure (HF) includes monitoring symptoms for deterioration in HF and having an appropriate response time in contacting their health care provider. One of the main principles of a heart failure clinic is to provide a structured education programme for the patient regarding self-care. Patient education is the leading intervention to equip patients with the skills for symptom recognition. The education aims to ensure the patient can recall the knowledge from memory if required. Purpose: The aim of this study was to evaluate patient knowledge, through testing memory, regarding symptom recognition in a single center HF clinic. To identify if there was a difference between attaining knowledge on symptom recognition gained through lived experience versus knowledge on symptom recognition gained through education. Methods: 50 patients were recruited for this study. Average age was 72 years old. 38 male and 12 female. All participants had previously experienced at least one symptom of HF. All participants had a minimum of 2 education sessions in the HF clinic. All patients had evidence from their weight logbook of daily weight monitoring. Question "a" tests knowledge acquired from education and question "b" tests knowledge acquired from lived experience. All participants were asked two questions: a) what is the amount of weight increase you are monitoring for? b) name one symptom you are monitoring that would indicate possible deterioration in HF. Results: single center prospective analysis Question a: 35% answered correctly Question b: 82% answered correctly Conclusions: Processes of learning and the transfer of learning are central to understanding how people can achieve competency in self-care. In this study patients seem to remember information better from a lived experience rather than trying to recall taught information. It important to identify the patients' individual factors and needs to successfully support their self-care management. Further evaluation of assessing the implementation of other supports available such as, mobile Apps and multimedia-based education, to address knowledge recall deficits is needed to determine if they aid the patient to achieve competency in self-care.